A highly efficient needle-free-injection delivery system for mRNA-LNP vaccination against SARS-CoV-2. (February 2023) - Mao, Shanhong; Li, Shiyou; Zhang, Yuxin; Long, Luoxin; Peng, Junfeng; Cao, Yuanyan; Mao, Jessica Z.; Qi, Xin; Xin, Qi; San, Guoliang; Ding, Jing; Jiang, Jun; et al.
Abstract: Despite the various vaccines that have been developed to combat the coronavirus disease 2019 (COVID-19) pandemic, the persistent and unpredictable mutations of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) require innovative and unremitting solutions to cope with the resultant immune evasion and establish a sustainable immune barrier. Here we introduce a vaccine-delivery system with a combination of a needle-free injection (NFI) device and a SARS-CoV-2-Spike-specific mRNA-Lipid Nanoparticle (LNP) vaccine. The benefits are duller pain and a significant increase of immunogenicity compared to the canonical needle injection (NI). From physicochemical and bioactivity analyses, the structure of the mRNA-LNP maintains stability upon NFI, contradictory to the belief that LNPs are inclined towards destruction under the high-pressure conditions of NFI. Moreover, mRNA-LNP vaccine delivered by NFI induces significantly more binding and neutralizing antibodies against SARS-CoV-2 variants than the same vaccine delivered by NI. Heterogeneous vaccination of BA.5-LNP vaccine with NFI enhanced the generation of neutralizing antibodies against Omicron BA.5 variants in rabbits previously vaccinated with non-BA.5-specific mRNA-LNP or other COVID-19 vaccines. NFI parameters can be adjusted to deliver mRNA-LNP subcutaneously or intramuscularly. Taken together, our results suggest that NFI-based mRNA-LNP vaccination is an effective substitute for the traditional NI-based mRNA-LNP vaccination. Graphical Abstract: ga1 Highlights: Needle-free mRNA vaccine delivery system provides better immunogenicity than needle injection. LNP booster substantially increases the neutralizing antibody titers against Omicron BA.5 upon heterogenous vaccination. Multiple injections at different sites in one vaccination could be a more effective option for future immunization process. An optimized needle-free system minimizes the deformation of mRNA nanoparticles